2001
DOI: 10.1143/jjap.40.2197
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Diffusion through SiO2 from a Hydrogenated Amorphous Carbon Layer and Accumulation at the SiO2/Si Interface

Abstract: Carbon diffusion in a SiO 2 /Si system was investigated. The source was provided by chemical vapor deposition of a hydrogenated amorphous carbon layer onto the oxide at low temperature. From layers with low oxygen content, no carbon outdiffusion was detected up to 1190 • C. If the O content was high, the diffusion would start suddenly at 1140 • C, and carbon accumulation would be found on the Si side of the SiO 2 /Si interface in the form of SiC precipitates. These results are interpreted by assuming oxygen-as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 8 publications
1
11
0
Order By: Relevance
“…Our findings regarding the CO extraction and diffusion are in good qualitative agreement with the results of experiments Krafcsik et al 2,31 which indicate that carbon diffusion does not start through high-quality SiO 2 up to temperatures in excess of 900°C, 32 but then it proceeds very fast. They also show that at the temperature used for the oxidation of SiC (Ϸ1200°C), the removal of carbon from the interface should not be limited by the diffusion of C through the oxide.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Our findings regarding the CO extraction and diffusion are in good qualitative agreement with the results of experiments Krafcsik et al 2,31 which indicate that carbon diffusion does not start through high-quality SiO 2 up to temperatures in excess of 900°C, 32 but then it proceeds very fast. They also show that at the temperature used for the oxidation of SiC (Ϸ1200°C), the removal of carbon from the interface should not be limited by the diffusion of C through the oxide.…”
Section: Discussionsupporting
confidence: 92%
“…The highest barrier in this diffusion process is 2.7 eV. These results show that carbon atoms can be removed from a continous network of SiO 2 with an activation energy between 2.7 and 3.1 eV. On the other hand, CO can diffuse with a very low ͑0.4 eV͒ barrier in silica.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…It was demonstrated that diffusing carbon in a fused quartz substrate is often bonded to oxygen by C-O complexes. 24 Therefore, oxygen concentration should be considered in further work.…”
Section: Comparison With Other Recent Resultsmentioning
confidence: 99%